Pemanfaatan Eceng Gondok, Lidah Mertua, dan Kangkung sebagai Agen Bioremediasi Limbah Cair Rumah Tangga - Putriana, Delvi; Salsabila, Gina; Khosi'in (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of Eichhornia crassipes (water hyacinth), Sansevieria trifasciata (snake plant), and Ipomoea aquatica (water spinach) as bioremediation agents for household wastewater, particularly laundry effluent containing detergent residues. The purpose of this research is to identify which plant species can best improve water quality by stabilizing pH levels, increasing clarity, and supporting plant growth. The study was conducted using an experimental laboratory method with a quantitative descriptive approach. Each plant was placed in a container filled with 500 mL of laundry wastewater, and parameters such as pH, water color, and plant growth were observed over three days. Data were analyzed descriptively to compare the bioremediation performance of each plant. The results showed that Sansevieria trifasciata was the most effective plant in improving water quality, as indicated by an increase in pH from 6 to 7, clear water appearance, and optimal plant growth (52 g). Eichhornia crassipes maintained stable pH values (6) but produced slightly turbid water, while Ipomoea aquatica resulted in increased turbidity and decreased pH (5). These findings suggest that the bioremediation process strongly depends on plant structure and metabolic activity. Snake plant, with its dense root system, demonstrated a higher ability to absorb and neutralize chemical pollutants compared to the other two species. Overall, Sansevieria trifasciata shows great potential as a simple, low-cost, and environmentally friendly bioremediation agent for household wastewater treatment.